Antipyretic activity test of cucumber (Cucumis sativus L.) ethanol and methanol extract on male white mice (Mus musculus) - Arifianto, Nasruhan; Saputri, Chairunisa Ayu; Retnosari, Ferra; Meidina, Hayu; Wahyuni, Wahyuni (Sasambo Journal of Pharmacy, 2024)
Cucumber plants are annual plants that grow in the lowlands or highlands. Cucumbers are easy to get and have lots of benefits, but the peel of the cucumber is still less desirable, so it becomes waste. On the peel of cucumber (Cucumis sativus Linn) showed the active compounds of saponins, phenolics, steroids, protein, calcium and flavonoids. Compounds that have an antipyretic effect are flavonoid compounds. The aim of the research was to determine the ability of the methanol and ethanol extracts of cucumber peels as antipyretics. This study was included in an experimental study by looking at the effect of methanol and ethanol extract cucumber peels on male mice. The method used is chemical induction method. Forty male mice with body weight between 20-30 grams, divided into 8 groupsnegative control, positive control, cucumber peel methanol and ethanol extract dose of 100 mg/kg BW, 200 mg/kg BW, 400 mg/kg BW. The decrease in temperature was observed for 180 minutes with an interval of 30 minutes. It is known that at 30 minutes it has shown a decrease in temperature, until at 240 minutes the temperature drop has reached normal temperature. The data obtained were analysed statistically with One-way ANOVA. The results showed that cucumber peel extract (Cucumis sativus Linn) could provide antipyretic activity at doses of 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW in peptone-induced male mice (Mus musculus), by injecting subcutaneously in the nape of the mice. Â The effective dose Cucumber peel of Ethanol and Methanol extract (Cucumis sativus L.) used to reduce the rectal temperature of male white mice is at a dose of 400 mg/Kg BW